NATURAL DYE’S SAFE AND ECO-FRIENDLY - Rajbhar,, Karishma; Dawda, Dr. Himanshu; Mukundan, Dr. (Mrs.) Usha (IJRDO-Journal of Applied Science, 2016)
Natural dyes present in plants pigments like betalaines, xanthophylls, anthocyanins,chlorophylls, tannins, flavonoids, etc can be used as natural colours for various industries likefood, beverages, cosmetics, textiles etc. As manufacturing and disposal of the enormouseffluents formed during synthetic dye are affecting environment. Natural dyes can be rescueto us if used in smart manner. Waste vegetables and others plant product damaged duringtransportation used as a source of natural dye. The results are incredible and are also safe forskin and do not cause any allergies. Natural dyes are also eco-friendly, thus helping us to saveour nature.